Handshake, No. 10 (July 2013) - International Finance Corporation (International Finance Corporation, Washington, DC, 2015)
This paper includes the following headings: education public, private, and partnerships, or PPPs come of age; vouching for the future; mobile learning dials up success; U.S. Secretary of Education by Arne Duncan; perspective; compass; and legalese.